Women's leadership in a charging world / Ana María Brasileiro - Barsileiro, Ana Maria (Japón, 1996)
Introduction.Can women change hte world
Col. Gen
Keywords: 1. GENERO E INTERCULTURALIDAD 2. MUJER ACTIVIDAD POLITICA 3. DERECHO DE LA MUJER